Analysis of leaf forage value and screening of different populations of Pteroceltis tatarinowii, a rare and endemic species in China - Gao, Yun; Cheng, Tian-Tian; Zhang, Chun-Xiang; Yan, Yu; Zhang, Lin; Liu, Qing-Zhong; Liu, Yan; Qiao, Qian (Frontiers in Plant Science, 2023)
To fully exploit the economic value of the Chinese endemic species Pteroceltis tatarinowii and provide new resources for forage production, the forage nutritional value of P. tatarinowii leaves from different populations was analyzed and evaluated. The results were as follows: 1) There were significant differences in the forage nutrient indices of leaves from different populations. The crude protein content was 10.77%–18.65%, with an average of 14.58%, and the SDJN population had the highest crude protein content. The average crude fat, crude fiber content was 7.62%; the average neutral detergent fiber content was 25.33%; and the average acid detergent fiber contents were 6.79%, 7.62%, 25.33%, and 17.52%, respectively. The average phosphorus and calcium content in the leaves was 0.785 g·kg−1 and 58.01 g·kg−1, respectively. The tannin content was much lower than the antifeedant standard, at an average of 4.97 g·kg−1. The average total amounts of hydrolyzed and free amino acids in the leaves were 108.20 mg·g−1 and 47.87 mg·g−1, respectively. Thus, P. tatarinowii leaves have high crude protein, crude fat, and calcium contents, and low fiber, tannin contents, and are protein-rich. These results provide evidence that this species can be developed into an excellent woody forage tree. 2) There were significant differences in the forage quality evaluation indices among the populations. The forage indices of NDP, ADP, DMI, DDM, and RFV of 21 populations all met the super standard of the American Grass and Grassland Association (AFGC) for hay, two crude protein indices met the grade 1 standard, and 12 crude protein indices met the grade 2 standard. Four high-protein and high-RFV forage populations (SDJN, SDZZ, SXLQ, and AHXX) were selected. 3) The results of the correlation analysis showed that there was no significant correlation between the forage characteristics of P. tatarinowii leaves and latitude and longitude, indicating no significant geographical variation. However, the forage characteristics were strongly correlated with elevation, average annual temperature, and annual precipitation. Thus, high elevation, low temperatures, and rainy weather can improve the forage value of the leaves. P. tatarinowii can be planted to provide leaf forage in cold and wet areas at a specific elevation. Moreover, the forage value of P. tatarinowii leaves can be further improved by increasing nitrogen fertilizer and reducing K and Ca fertilizers during cultivation. 4) Cluster analysis revealed obvious regionalism. Taking the Yangtze River Basin as the limit, cluster analysis divided the species into four population groups: the Yangtze River Basin and northern, southwestern, and eastern coastal populations.